Doped Emitting Cesium Silver Halides as X‐Ray Scintillator with Fast Response Time, High Absorption Coefficient, and Light Yield. Issue 9 (26th July 2021) - Yao, Jia-Li; Zhang, Zi-Xu; Sun, Xiao-Qi; Chang, Tong; Guo, Jing-Fu; Huang, Ke-Ke; Zeng, Hai-Bo; Wang, Da-Yang; Yang, Wen-Sheng; Zeng, Ruo-Sheng; Li, Xiao-Ming; Xie, Ren-Guo
Abstract : Radioluminescence materials (scintillators) are widely investigated because of their potential application in many fields, such as medical imaging, security‐related techniques, and nondestructive inspection. However, the fabrication of scintillator materials with simultaneously fast response time, high absorption coefficient, and high light yield, as well as low toxicity is still a challenge. Herein, the synthesis of Cu(I)‐doped Cs2 AgI3 single crystals (SCs) with a 1D crystal structure is presented. A bright blue‐green photoluminescence (PL) is observed after incorporating Cu + into the Cs2 AgI3 SCs under UV irradiation at room temperature. The PL quantum yield of the doped samples can reach up to 73% at a Cu + concentration of 0.66%. Experimental and theoretical studies show that the blue‐green emission may originate from self‐trapped excitons, which is further verified by photophysical results from control experiments on pure Cs2 AgI3 SCs. Upon X‐ray excitation, Cu‐doped SCs exhibit fast scintillation decay time (288 ns), high light yield (27 000 photons per MeV), and high absorption coefficient compared with the commercial product (CsI: Tl). These results suggest that Cu‐doped Cs2 AgI3 is an ideal scintillator, which will be a promising candidate for potential application in dynamic real‐time imaging and radiation detection. Abstract : Cu(I)‐doped Cs2 AgI3 crystals show bright blue‐green emission at 488 nm, which originates from self‐trapped excitons as verified by photophysical studies. The as‐prepared sample exhibits fast decay time (288 ns), high light yield (27 000 photons per MeV), and high absorption coefficient. These results suggest that Cu‐doped Cs2 AgI3 will be a promising candidate for X‐ray imaging applications.